Need Analysis of Arabic Learning in MI for the Development of Collaborative Interactive E-Modules FAL (Fun Arabic Learning): Analisis Kebutuhan Pembelajaran Bahasa Arab di MI untuk Pengembangan E-Modul Interaktif Kolaboratif FAL (Fun Arabic Learning) - Nailul Hidayah; Nurhidayati Nurhidayati; Kholisin Kholisin; Pabiyah Toklubok (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
Arabic language learning in Madrasah Ibtidaiyah (MI) still faces various challenges, including the lack of learning media that is interesting and in accordance with the needs of students. This study aims to analyze the needs and problems in Arabic language learning in Madrasah Ibtidaiyah (MI) as a first step in the development of collaborative interactive e-modules FAL (Fun Arabic Learning). The research employs a descriptive qualitative method with a preliminary study approach. Data were gathered through observations, interviews, and questionnaires administered to teachers and students. The data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and method triangulation. The results showed that students had difficulty in understanding Arabic vocabulary and sentence structure, low motivation to learn due to limited learning media, lack of collaborative activities to improve Arabic language skills. Teachers also experience obstacles in delivering material interactively and collaboratively. Therefore, the development of collaborative interactive e-modules FAL (Fun Arabic Learning) is expected to be an innovative solution To enhance the efficiency and appeal of Arabic language learning in MI. Keywords: Arabic Language Learning, Collaborative, Fun Arabic Learning, Interactive E-Module